Atmospheric boundary layer simulation in a new open-jet facility at LSU: CFD and experimental investigations. (November 2017) - Aly, Aly Mousaad; Gol-Zaroudi, Hamzeh
Highlights: Turbulence intensity profiles obtained by LES are in a good agreement with theoretical profiles. LSU open-jet permits testing larger models with less sensitivity to blockage restrictions. CFD schemes are potential in the design of open-jet simulators. CFD reduces the effort required to experimentally simulate near ground ABL wind flows. Abstract: This study focuses on Computational Fluid Dynamics (CFD) investigations of atmospheric boundary layer (ABL) wind generation with proper flow characteristics for an open-jet setup design. The results of two-dimensional and three-dimensional numerical CFD models were later validated experimentally within a newly built open-jet facility at Louisiana State University (LSU). Various turbulence models of k – ɛ, Reynolds Stress Model, and Large Eddy Simulation (LES) are implemented to help selecting appropriate flow management schemes. Based on CFD results, the planks' configuration that matched open terrain was a set of angles: 15°, 12°, 10°, 5°, 0°, 0° from bottom to top. The LES simulated wind velocity and turbulence intensity profiles were in good agreements with target profiles for open-terrain, because LES uses a spatial filtering operation to separate the larger eddies (which are more anisotropic) and smaller eddies (which are nearly isotropic). Moreover, a comprehensive experimental flow quality check was conducted, and the facility was further calibrated by testing a 1:15 scaled model of a low-rise building. The results were then compared with the National Institute of Standards and Technology, and the University of Western Ontario wind-tunnel database. It was shown that the general patterns of pressure coefficient's contours are more symmetric for LSU model and the reattachment patterns are identical between the two cases. Eventually, the potential application of CFD was proved when implemented in the design of an open-jet facility to reduce the experimental effort for ABL wind processes.